2021
DOI: 10.2196/14088
|View full text |Cite
|
Sign up to set email alerts
|

Role of Health Literacy in Health-Related Information-Seeking Behavior Online: Cross-sectional Study

Abstract: Background The internet has emerged as a main venue of health information delivery and health-related activities. However, few studies have examined how health literacy determines online health-related behavior. Objective The aim of this study was to investigate the current level of health-related information-seeking using the internet and how health literacy, access to technology, and sociodemographic characteristics impact health-related information-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 37 publications
6
53
2
Order By: Relevance
“…Health literacy is a construct that formulates from early adolescence and develops across the life-course. 17 It relates to poor health-related behaviour, 27 inappropriate health-information seeking behaviour, 28 delayed healthcare visit and forgone treatment. 29 Therefore, by the late middle age, as is our participants, low health literacy may have already resulted in poorer health in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is a construct that formulates from early adolescence and develops across the life-course. 17 It relates to poor health-related behaviour, 27 inappropriate health-information seeking behaviour, 28 delayed healthcare visit and forgone treatment. 29 Therefore, by the late middle age, as is our participants, low health literacy may have already resulted in poorer health in some individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Three-fourth of Malaysians are now smartphone users, with most (60.9%) of them in the lowest income group [ 18 ]. Although health-related information-seeking behavior on the internet is greater in those with good health literacy [ 19 ], our previous qualitative work among people with limited health literacy suggests that a mobile app is a preferred medium to deliver supported self-management, including a pictogram-based asthma action plan and signposting to reliable asthma information sources.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Diviani et al [13] found that low health literacy and related skills were negatively related to the ability to evaluate web-based health information and trust such information. Lee et al [14] investigated the level of seeking health-related information on the internet and how health literacy, access to technology, and sociodemographic characteristics impact behaviors related to seeking health-related information. Additionally, Ridout and Campbell [15] reviewed relevant research on young people's acquisition of health information from social networking sites and found that social networking site-based interventions were highly usable, engaging, and supportive for young people.…”
Section: Introductionmentioning
confidence: 99%